Rating methodology for real estate markets – Poland case study - Renigier-Biłozor, Malgorzata; Wisniewski, Radoslaw; Kaklauskas, Arturas; Biłozor, Andrzej (International Journal of Strategic Property Management, 2018)
The development of the real estate market is conditioned by a variety of endogenous and exogenous factors. Selected factors determine the local character of the real estate market, whereas others contribute to its classification as one of the main branches of the national economy. Rapid economic growth and the search for new investment opportunities have turned the real estate market into a highly competitive arena where various players carry out diverse investment strategies. Investors search for similarities that would enable them to develop risk minimizing strategies. Ratings are a modern tool that can be deployed in analyses and predictions of real estate market potential. This paper proposes a methodology for developing real estate market ratings, and it identifies the types of information and factors which affect decision-making on real estate markets. The following research hypotheses are formulated and tested in the article: 1) a real estate market can be rated in view of its significance for the local and national economy, 2) real estate market ratings support market participants in the decision-making process. First Publish Online: 20 Jun 2014